Fish, fisheries and land use at Sukau, lower Kinabatangan floodplain, Sabah - Muhamad Saini, b. Suliansa (Universiti Malaysia Sarawak (UNIMAS), 2004)
A total of 23600 ha of land area (10.28%) around Sukau have been cultivated by oil palm. The active large agriculture plantations have direct affects to the lower Kinabatangan River and aquatic habitats around Sukau. Only 18.1% of land area falls under Landsat TM undisturbed category. A total of 8.0% was under active land clearing in year 2002 Landsat TM image. A total 11 families and 26 species of fish have been identified during this study. Cyprinidae followed by Bagridae and Siluridae represent the dominant fish species in the study area. The overall Shannon Weiner's Index of Diversity of fish fauna in Sukau is 1.9579, while Richness Index recorded at 2.3005 and the Evenness Index is 0.8097. In general, the fisheries aspects in Sukau are still in small scale with low fishing efforts, thus suggesting a low exploitation rate. Fishing activities still can be considered as only support the local livelihoods. The in-situ water quality reads narrow range of difference at all sampling sites and within the acceptable range of the Malaysia INWQS Class II limit. Large scale plantations without proper mitigation measures to conserve the aquatics environment in Sukau are perceived to have greater adverse impacts in the future.